Implementation of Special Autonomic Policies in the Health Sector in Teluk Wondama District, West Papua Province - Eduard Nukaki; Murtir Jeddawi; Djohermansyah Djohan; Hironymus Rowa (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this research is to analyze and explain the implementation of special autonomy policies in the health sector, the factors that influence the implementation of policies and formulate a new model of health services about the implementation of special autonomy policies in the health sector in Teluk Wondama Regency, West Papua Regency. This study uses Grindle's policy implementation theory, which consists of policy content and context. The research approach used in this research is a qualitative approach with a descriptive research type. The data analysis technique used is data reduction and concluding. The field research found that implementing the special autonomy policy in the health sector does not stand alone but involves many components (authorities, affairs, finances, resources, attitudes of implementers, community participation, and so on). Therefore, the special autonomy policy in the health sector can be seen as a system consisting of many interrelated components and runs continuously and is never final.